AN ONLINE CREDIT AGREEMENT WITH COLLATERAL IN INDONESIA - Ma’ruf Akib (International Journal of Law Reconstruction, 2021)
Along with the rapid development of information technology which in turn has an impact on economic activity around the world, financial technology is here to provide facilities in the provision of financial services for the community. The ease of convenience offered through unsecured online loans carries the risk of loan defaults made by debtors. The purpose of this research is to find out what is the urgency of the need for collateral as one of the requirements for submitting online loans and how online registration of fiduciary collaterals can be a preventive measure for bad credit in online credit distribution. This study uses a normative-juridical research method. The result of this research is that there is a collateral that the online lending agreement functions as a legal umbrella so that debtors' obligations to creditors are fulfilled so that they avoid default, default, and even investor losses in Fintech P2P Lending activities. The importance of having a fiduciary collateral that is registered in the credit agreement online is to avoid a legal vacuum (rechts vacuum) or legal vacuum (wet vacuum) when there is default or default by the debtor.